Integration of Life Sciences and Biotechnological Techniques in Plant Protection and Environmental Pollutant Management - Maryam Ibrahim Shakir; Israa Noori Farman Samin; Huda Muhammad Ail Abed Madi; Alia Hassan Hadi Karo (American Journal of Biodiversity, 2025)
Environmental health encompasses the protection of air, water, soil, food, climate, and ecosystems to safeguard public welfare and ecosystem functions. Contaminated environmental components undermine food, beverage, and recreational safety, pose health hazards for humans and animals via diverse exposure routes, threaten biodiversity and ecosystem services, and harm sustainable resource investment and recovery. Pollutants are classified by source (agricultural, domestic, industrial, and environmental), environmental phase (gaseous, liquid, solid), and impact (toxicity, bioaccumulation, persistence). Pollutant management directly intersects with biotechnological tools for increasing environmental resilience, stress tolerance, contamination resistance, and treatment remediation. This integration advances resource use without compromising environmental health while enabling sustainable agricultural practice adoption, guiding research along specified and coordinated pathways. Convergence among life sciences, biotechnology, ecology, and policy promotes seamless introduction, dissemination, and adoption of integrated practices. Development trajectories prioritizing one discipline while neglecting others lead to incomplete adoption, ineffective solutions, and unacceptable risks. Stakeholder expectation for science-led outreach further emphasizes this need. Detailed options for stakeholder engagement and dissemination are addressed through integrated sustainable-agriculture strategies, ensuring wide cross-disciplinary relevance